Physical and chemical characterisation of bullet impact holes on sheet metal surfaces by 9 mm calibre bullets - Malik, Syamsul Anuar Abd (2019)
Forensic investigators are currently facing challenges to determine bullet holes due to the variety of bullet type that have caused damage on a target, especially in cases involving drive-by shooting, ambush shooting, as well as cross fire shooting related to vehicle. It is rising trend in murder cases where the victim was sitting inside a vehicle. With a variety of bullet types available in the market, whether with the same or different calibres, it is difficult to definitely confirm a bullet hole, and also to determine the bullet types that caused that hole. In view of this, this study was aimed to characterise bullet impact holes made by 9 mm calibre ammunition on two different automotive doors through physical and chemical means. In this study, visual and macroscopic techniques was used to observe the morphological features of impact holes, as well as the application of scanning electron microscopy-energy dispersive x-ray (SEM-EDX) method to determine the inorganic elemental composition of samples recovered from the impact holes. Substantial differences among the bullet impact holes were successfully disclosed upon physical examination by observing the unique characteristics on each bullet hole, in term of the bullet hole diameter, height of the bullet crater, petalling effect, radial edge pattern, internal circumference pattern, crown or metallic ring formation, as well as the distribution of bullet dust residues around the bullet hole. Besides, elemental analysis revealed that certain projectile could have contained different composition of inorganic elements, as observed in polymer (ARX) type bullet with no lead was detected but with the presence of sulphur, which have been transferred to the bullet hole. Copper and zinc were detected in samples recovered from impact holes made by all projectiles, except lead round nose (LRN) type projectiles due to unjacketed property. In conclusion, morphological features of the produced impact holes could allow for exclusion of certain projectile types, and subsequently SEM-EDX further discriminated unjacketed projectile from those bullet holes made by jacketed projectiles. Bullet hole produced different types of 9 mm calibre ammunition could be characterised through physical examination and elemental analysis, possessing great potential in investigating the forensic evidence frequently encountered in shooting cases.